Wagering on the wallflower - Shepherd, Eva (Shepherd, Eva. Young Victorian ladies., 2021)
"A wallflower and an elegant gentleman... Gauche Hazel Springfeld is reconciled to being left on the shelf. At a society ball, she is improbably asked to dance by charismatic Mr. Lucas Darkwood. When she discovers it was all for a wager--he'll win a prize if he can turn her into marriage material--Hazel plans to get her own back! She'll frighten Lucas into thinking she really does expect that proposal-- from him!"--Provided by publisher.